EUCARPIA XIVth. Meeting on Capsicum and Eggplant genetics and breeding - V.M. Verba; T.P. Suprunova; E.A. Dzhos (Овощи России, 2010)
On 30th August-lst September 2010 the EUCARPIA XIVth Meeting on Genetics and Breeding of Capsicum and Eggplant was held in Valencia, Spain and focused on the enhancement of genetic recourses and practical aspects of Capsicum and Eggplant breeding.